Is There a Political Dynasty in The Head Village Election with Family Ties Candidates?: A Case Study in Pliken Village Banyumas - Widyastuti, Tri Rini; Wardiyono, F.X; Sutoyo, Ignatius Suksmadi (Universitas Negeri Semarang, 2022)
This paper is about the rise of political dynasties in Indonesia. This phenomenon has become increasingly public attention since the nomination of President Joko Widodo’s son and son-in-law in the regional election in Solo and Medan. The village that has been considered far from the hustle and bustle of national politics also shows a similar phenomenon, namely the emergence of candidates for village head (kepala desa/kades) who are still related to family (pilkades sedarah).[1] But is pilkades sedarah a reflection of the existence of the political dynasty? This paper examines the village head election in Pliken Village, Banyumas Regency, which presents a married couple as village head candidates, using a qualitative approach. Collecting data through in-depth interviews, FGDs, observation, and documentation. The result of the study shows that the emergence of pilkades sedarah is not due to the existence of a political dynasty, but rather as pragmatic and rational reasons. Proposing a wife as a “competitor” is a pragmatic attitude just to get around the rules that prohibit a single candidate in village head election. The absence of other candidates who dared to oppose the incumbent was due to the rationality of the people who saw the high cost of candidacy which was not proportional to the official income of the village head. They also assessed that the prestige of the incumbent village head was high, both in terms of educational qualifications and achievements, so that the opponent’s chances of winning the competition were small.Keywords: political dynasty, village head election, blood relation[1] Pilkades sedarah is a term to describe that village head candidates still have family or blood relations.